Development of European Educational Policy: Legal Foundations - Holubnycha, Liudmyla; Besarab, Tetiana; Moshynska, Olena (Educational Challenges, 2023)
The manuscript is devoted to European educational policy through the prism of legal regulations as their influence is very significant for the development of educational system especially at the tertiary level. The purpose is to study peculiarities of the shaping and development of European educational policies within the realm of higher education, where legal and pedagogical sciences intersect. The tasks are: to find out what place educational sector takes in Europe and why; to reveal the most significant legal documents in the sphere of education and follow the path of development of European policy development in the higher education domain by drawing insights from these documents; to determine the value of legal documents in the sphere of education for the development of European educational policy, based on their essence. The research methods used are analysis and syntheses of European legal documents related to the higher education field aimed at collecting the materials for researching the problem both from a legal and pedagogical position and for drawing the conclusion. The results revealed that the beginning of the European countries’ cooperation in educational sphere (1970s) led to the development of a common educational strategy. Enhanced collaboration in higher education across various tiers evolved significantly following the recognition of the pivotal role played by skilled human resources in driving economic and social progress, a realization that first emerged in 1985. This recognition led to the endorsement of several significant agreements, including the Single European Act in 1987, the Magna Charta Universitatum in 1988, and the Memorandum of Higher Education in the European Community in 1991. The most important EU Treaties concerned the educational sector as well that led to the signing the Bologna Declaration, the establishment of the European Higher Education Area, and the regular meetings of the European Ministers of Education. Education has become the basis for shaping European community and the core for economic stability. The conclusion is that European statesmen consider the educational sector to be the key one because it is the basis of economic, social and human development; the EU Higher Educational Policy has gone from the auxiliary industry in the context of shaping the internal market (1950s) to one of the priority sectors that is developing in response to the demands of society.